2016
DOI: 10.1016/j.pneurobio.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43/FUS in motor neuron disease: Complexity and challenges

Abstract: Amyotrophic lateral sclerosis (ALS), a common motor neuron disease affecting two per 100,000 people worldwide, encompasses at least five distinct pathological subtypes, including, ALS-SOD1, ALS-C9orf72, ALS-TDP-43, ALS-FUS and Guam-ALS. The etiology of a major subset of ALS involves toxicity of the TAR DNA-binding protein-43 (TDP-43). A second RNA/DNA binding protein, fused in sarcoma/translocated in liposarcoma (FUS/TLS) has been subsequently associated with about 1% of ALS patients. While mutations in TDP-43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
122
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(126 citation statements)
references
References 289 publications
1
122
0
Order By: Relevance
“…To date, however, few studies have attempted to identify upstream regulatory factors of XOR and BTN. Encoded by the Tardbp gene, TDP-43 is well recognized as an essential factor in amyotrophic lateral sclerosis and frontotemporal lobar degeneration 55,56 . Previous studies have shown that TDP-43 is involved in the progression of breast and other cancers 29,57,58 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, however, few studies have attempted to identify upstream regulatory factors of XOR and BTN. Encoded by the Tardbp gene, TDP-43 is well recognized as an essential factor in amyotrophic lateral sclerosis and frontotemporal lobar degeneration 55,56 . Previous studies have shown that TDP-43 is involved in the progression of breast and other cancers 29,57,58 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with tau, which is widespread in neurons and important in the assembly and stabilisation of microtubules [27,51], both TDP-43 and FUS have more specific roles, TDP-43 in mRNA function, DNA repair, and in non-coding RNA metabolism [45] while FUS is important in regulating gene expression including transcription, splicing, and RNA transport [31]. In both TDP-43 and FUS, nuclear clearance results in the immediate aggregation in the cytoplasm of cells [33]. In addition, TDP-43 can also repress non-conserved cryptic axons, many of which are cell type specific, and therefore loss of TDP-43 function could result in the degeneration of specific groups of cells [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Like TARDBP, mutations in FUS have been linked more closely to ALS, though positive protein aggregates for FUS appear in both ALS and FTLD [9]. FUS-positive inclusions account for about 5-10% of FTLD cases [9] and 1% of ALS cases [15]. Several proposed mechanisms link FUS to disruption of the autophagy-lysosome pathway.…”
Section: Fusmentioning
confidence: 99%
“…Each disease is also subdivided by molecular pathology depending on the primary components of inclusion bodies, such as Tau, TDP-43 (TAR DNA-Binding Protein 43), FUS (fused in sarcoma), SOD1 (superoxide dismutase 1 ) and C9 or f72 dipeptide repeats (DPRs) [9,15]. In 2006, both ALS and FTLD were found to have neuronal inclusions composed largely of TDP-43, an RNA-binding protein, that are also ubiquitin and p62-positive, suggesting that these aggregates were tagged for degradation [16][17][18].…”
Section: Introductionmentioning
confidence: 99%